2014
DOI: 10.5755/j01.ss.84.2.7492
|View full text |Cite
|
Sign up to set email alerts
|

Training Services in Small and Medium-sized Enterprises: Evidence from Poland

Abstract: In the knowledge-based economy knowledge and skills are becoming more and more significant for the success of companies. This applies also to firms from small and medium-sized enterprises (SMEs) sector. As large companies in many cases posses special divisions devoted to trainings, they normally have no problems with updating the knowledge and skills of their employees. The situation is different with regard to SMEs, which often have no resources and abilities to train their employees. In the article, the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Most of the previous research on the use of multimedia audio/video in education focused on the discussion of school education (Lohmann and Frederiksen, 2018;Kincey et al, 2019;Matsiola et al, 2019;Mei et al, 2019;Ocak and Baran, 2019) but rarely discussed education and training in enterprises. However, research indicated that employees participating in education and training can improve in terms of productivity (Becker, 1962;Smith and Kenyon, 2005;Zieba and Zieba, 2014), ability and knowledge (Mann and Robertson, 1996;Huang, 2001), and self-efficacy (Mann and Robertson, 1996). Nevertheless, previous literature scarcely mentioned improving the effectiveness of training styles nor the enhancement of employees' job involvement, organizational commitment, and satisfaction with self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous research on the use of multimedia audio/video in education focused on the discussion of school education (Lohmann and Frederiksen, 2018;Kincey et al, 2019;Matsiola et al, 2019;Mei et al, 2019;Ocak and Baran, 2019) but rarely discussed education and training in enterprises. However, research indicated that employees participating in education and training can improve in terms of productivity (Becker, 1962;Smith and Kenyon, 2005;Zieba and Zieba, 2014), ability and knowledge (Mann and Robertson, 1996;Huang, 2001), and self-efficacy (Mann and Robertson, 1996). Nevertheless, previous literature scarcely mentioned improving the effectiveness of training styles nor the enhancement of employees' job involvement, organizational commitment, and satisfaction with self-efficacy.…”
Section: Introductionmentioning
confidence: 99%